Evaluation of the ex vivo Effects of Tamoxifen on Adipose-Derived Stem Cells: A Pilot Study - Boemi, Ilena; Lisa, Andrea Vittorio Emanuele; Vitali, Eleonora; Liman, Nurçin; Battistini, Andrea; Barbera, Federico; Maione, Luca; Vinci, Valeriano; Klinger, Marco Ettore Attilio; Lania, Andrea Gerardo Antonio (Frontiers in Cell and Developmental Biology, 2021)
Autologous fat grafting (AFG) is a safe and minimally invasive procedure to correct soft tissue defects. The benefit of AFG is attributed to adipose-derived stem cells (ASCs) in fat tissue graft. This technique is useful also in patients undergoing reconstructive surgery following quadrantectomy for breast cancer. However, these patients are frequently treated with tamoxifen. We evaluated the ex vivo effects of tamoxifen on ASCs to understand if cellular functions of ASCs are affected. We selected 24 female patients; 10 of which were breast cancer patients treated with quadrantectomy and tamoxifen. As control group, we selected 14 healthy female subjects (9 premenopausal and 5 menopausal). We found that tamoxifen has no effect on cellular proliferation, VEGF secretion or apoptosis of ASCs. The gene expression assessment demonstrated no impairment in differentiation capacity of ASCs. Our results showed that tamoxifen has no effect on cellular functions of ASCs for the first time in an ex vivo single-center study.